Childhood Socioeconomic Status and Depressive Symptoms of Young Adults: Mediating Role of Childhood Trauma - Yang, Caiyan; Chen, Peiyi; Xie, Junyi; He, Yongtong; Wang, You; Yang, Xueling (Frontiers in Psychiatry, 2021)
Background: Studies have shown that low childhood socioeconomic status (SES) is associated with a high prevalence of depressive symptoms. Childhood trauma, as a potential consequence of low SES, may play an important part, but the mediation effect of childhood trauma remains to be elucidated. Methods: A cross-sectional survey was conducted among 1807 university students. The MacArthur Scale of Subjective Social Economic Status – Youth Version, Childhood Trauma Questionnaire, and Beck Depression Inventory were used to measure childhood SES, childhood trauma, and current depressive symptoms, respectively. A structural equation model (SEM) was employed to demonstrate the mediating role of childhood trauma on the association between childhood SES and depressive symptoms. Results: The SEM demonstrated that childhood SES had significant indirect effects upon depressive symptoms via childhood trauma. Childhood trauma accounted for 89.3% of the total effect, indicating a profound mediation effect. Conclusions: The effect of childhood SES on the depressive symptoms of young adults was mediated by childhood trauma, which emphasizes the importance of early prevention and intervention of child neglect/abuse.